Artificial Light Increases Local Predator Abundance, Predation Rates, and Herbivory. Issue 6 (26th September 2019) - Mcmunn, Marshall S; Yang, Louie H; Ansalmo, Amy; Bucknam, Keatyn; Claret, Miles; Clay, Cameron; Cox, Kyle; Dungey, Darian R; Jones, Asia; Kim, Ashley Y; Kubacki, Robert; Le, Rachel; et al.
Abstract: Human activity is rapidly increasing the radiance and geographic extent of artificial light at night (ALAN) leading to alterations in the development, behavior, and physiological state of many organisms. A limited number of community-scale studies investigating the effects of ALAN have allowed for spatial aggregation through positive phototaxis, the commonly observed phenomenon of arthropod movement toward light. We performed an open field study (without restricted arthropod access) to determine the effects of ALAN on local arthropod community composition, plant traits, and local herbivory and predation rates. We found strong positive phototaxis in 10 orders of arthropods, with increased (159% higher) overall arthropod abundance under ALAN compared to unlit controls. The arthropod community under ALAN was more diverse and contained a higher proportion of predaceous arthropods (15% vs 8%). Predation of immobilized flies occurred 3.6 times faster under ALAN; this effect was not observed during the day. Contrary to expectations, we also observed a 6% increase in herbivory under ALAN. Our results highlight the importance of open experimental field studies in determining community-level effects of ALAN.